Amputation, Prosthesis Use, and Phantom Limb Pain An Interdisciplinary Perspective - Murray, Craig; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Amputation, Prosthesis Use, and Phantom Limb Pain An Interdisciplinary Perspective Edited by Craig D. Murray For the millions of patients adjusting to life with one or more missing limbs, adaptation involves an intricate network of physical, psychological, social, and existential factors. It is with this complex scenario in mind that Amputation, Prosthesis Use, and Phantom Limb Pain: An Interdisciplinary Perspective has been developed. Unlike other books that deal exclusively with one or another of these topics, this volume unites the three to return the experiential to what is often treated in the literature$1 (Band too often in the clinic$1 (Bas a solely medical condition. Written by top specialists in areas ranging from psychology and neuroscience to biomedical engineering and computer science (and including material applicable to those with congenital missing limbs as well as to amputees), this volume provides up-to-date knowledge with wide appeal to a variety of professional readers. In addition, the book$1 (Bs accessibility ensures that practitioners working in teams understand each other$1 (Bs work as well as client needs. Among the leading-edge topics: Ethical and medico-legal issues in providing assistive technology. Psychosocial assessment of adaptation to amputation and prosthesis use. Congenital limb deficiencies and experiences of prosthesis use. Prothesis use relating to the formation and maintenance of romantic relationships. Biopsychosocial approaches to postoperative pain. Phenomenology of phantom limb experience and prosthesis use. Relationship between coping style and phantom limb pain. Virtual-reality treatments for phantom limb pain. Must reading for clinical and health psychologists, neuropsychologists, prostheticians, orthopedists, neurologists, professionals in rehabilitation and rehabilitative medicine, and designers of assistive technologies, Amputation, Prosthesis Use, and Phantom Limb Pain is dedicated to the goal of encouraging proper fit and alignment$1 (Bnot only between patients and devices, but between healing professionals and their clients.s
Developing an Interdisciplinary Perspective on Amputation, Prosthesis Use, and Phantom Limb Pain: An Introduction -- Need-Directed Design of Prostheses and Enabling Resources -- Ethical and Medico-Legal Issues in Amputee Prosthetic Rehabilitation -- Monitoring of Upper Limb Prosthesis Activity in Trans-Radial Amputees -- Adaptation to Amputation and Prosthesis Use -- Understanding Adjustment and Coping to Limb Loss and Absence through Phenomenologies of Prosthesis Use -- Return to Work After Amputation -- Gender, Sexuality and Prosthesis Use: Implications for Rehabilitation -- Post Amputation Chronic Pain Profile and Management -- Phantom Limb Pain; Prevalence, Mechanisms and Associated Factors -- Management of Phantom Limb Pain -- Virtual Solutions to Phantom Problems: Using Immersive Virtual Reality to Treat Phantom Limb Pain.
Keywords: Medicine; Nursing; Rehabilitation; Biomedical engineering; Psychology, clinical; Medicine & Public Health; Rehabilitation Medicine; Health Psychology; Biomedical Engineering; Nursing